PENERAPAN ASSESSMEN KINERJA BERBASIS MODEL INQUIRY TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK MATERI ELASTISITAS DI SMA N 1 SIABU - Himsar, Himsar (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
The learning process through instant social media can foster selfishness and weak independence among students. Learning without a process of identifying problems, making hypotheses, and solving them leads to students being weak in critical thinking. Students’ performance becomes poor in problem-solving and teamwork among them diminishes. The implementation of performance assessment based on the guided inquiry model aims to develop students' scientific attitudes in solving problems independently. This research is quantitative in nature. The subjects of this study were students of class XI IPA 1 at SMA N 1 Siabu. This research used Classroom Action Research, which consisted of two cycles. The indicators of success in this study were an average score of 75 with a mastery level of 70%. Based on the results of the study, the average score for Cycle I on the performance assessment based on the guided inquiry model was 69.16 with a mastery level of 60%, which led to the continuation of Cycle II since it was below the success indicator. In Cycle II, the average score increased to 78.66 with a mastery level of 86.66%, indicating an improvement above the success indicator. The average critical thinking score in Cycle I was 72 with a mastery level of 66.66%, meaning it was not yet completed, so it continued to Cycle II. In Cycle II, the average score for critical thinking skills was 76.83 with a mastery level of 86.66%, thus indicating that the study was completed successfully.